Blocking cholesterol formation and turnover improves cellular and mitochondria function in murine heart microvascular endothelial cells and cardiomyocytes - Braczko, Alicja; Harasim, Gabriela; Kawecka, Ada; Walczak, Iga; Kapusta, Małgorzata; Narajczyk, Magdalena; Stawarska, Klaudia; Smoleński, Ryszard T.; Kutryb-Zając, Barbara (Frontiers in Physiology, 2023)
Background: Statins and proprotein convertase subtilisin/kexin type 9 inhibitors (PCSK9i) are cornerstones of therapy to prevent cardiovascular disease, acting by lowering lipid concentrations and only partially identified pleiotropic effects. This study aimed to analyze impacts of atorvastatin and synthetic peptide PCSK9i on bioenergetics and function of microvascular endothelial cells and cardiomyocytes. Methods: Mitochondrial function and abundance as well as intracellular nucleotides, membrane potential, cytoskeleton structure, and cell proliferation rate were evaluated in mouse heart microvascular endothelial cells (H5V) and cardiomyocytes (HL-1) under normal and hypoxia-mimicking conditions (CoCl2 exposure). Results: In normal conditions PCSK9i, unlike atorvastatin, enhanced mitochondrial respiratory parameters, increased nucleotide levels, prevented actin cytoskeleton disturbances and stimulated endothelial cell proliferation. Under hypoxia-mimicking conditions both atorvastatin and PCSK9i improved the mitochondrial respiration and membrane potential in both cell types. Conclusion: This study demonstrated that both treatments benefited the endothelial cell and cardiomyocyte bioenergetics, but the effects of PCSK9i were superior.